Positive Connection of Extensive Reading and Writing Fluency in EFL Learning - Nor Fitriansyah; M. Zaini Miftah (English Department of Faculty of Tarbiyah and Teacher Training, 2020)
Extensive reading and writing fluency in language learning get connected to each other. The benefits include gains in reading and writing competence and skills. However, how far they get connected in EFL learning has not been discussed so far. This study examined the connection of extensive reading and writing fluency of the thirty-two students of the English Education Department at a university in Palangka Raya Kalimantan Tengah Indonesia. The correlational design was applied in this study. The online Extensive Reading Test (ERT) developed by Extensive Reading Foundation was used to get the students' extensive reading scores. To gain the students' writing fluency scores, a Writing Fluency Test (WFT) was applied. For the data analysis, it used Pearson product-moment correlation. Results show that there is a moderate positive correlation between the students' extensive reading and writing fluency. It is indicated with rxy = 0.408 > rtable = 0.340 at 5%. In short, the extensive reading activities have a positive connection to the writing fluency of the students in language learning. Therefore, extensive reading activities should always be integrated with writing activities in the context of Indonesian EFL learning.